Call Center Productivity Over 6 Months Following a Standing Desk Intervention. Issue 2 (2nd July 2016) - Garrett, Gregory; Benden, Mark; Mehta, Ranjana; Pickens, Adam; Peres, S. Camille; Zhao, Hongwei
OCCUPATIONAL ABSTRACT: Stand-capable desks have been shown to successfully reduce sedentary behavior in the modern office, but whether their utilization improves cognitive productivity is not known. We compared productivity between stand-capable desk users and traditional seated desk users in a call center environment. Data were collected daily over a continuous 6-month period. We found that increased stand-capable desk use is a likely contributor to increased productivity over traditional seated desk use. These findings indicate that use of stand-capable desks as ergonomic interventions to improve physical health among employees may also positively impact their work productivity. TECHNICAL ABSTRACT Background : Many office employees are spending up to 90% of their workday seated, and employers are considering stand-capable desks as a way to increase physical activity throughout the day. When deciding on adoption of stand-capable workstations, a major concern for employers is that the benefits, over time, may not offset the initial cost of implementation. Methods: This study compared objective measures of productivity over time between a group of stand-capable desk users and a seated control group in a call center. Comparison analysis was completed for continuous 6-month secondary data for 167 employees, across two job categories. Results: Users of stand-capable desks were ∼45% more productive on a daily basis compared to their seated counterparts. Further, productivity of the stand-capable desk users significantly increased over time, from ∼23% in the 1st month to ∼53% over the next 6 months. Finally, this productivity increase was similar for employees across both job categories. Conclusions: These findings suggest important benefits of employing stand-capable desks in the work force to increase productivity. Prospective studies that include employee health status, perceptions of (dis)comfort and preference over time, along with productivity metrics, are needed to test the effectiveness of stand-capable desks on employee health and performance.